Alpha-lipoic acid improves sperm motility in infertile men after varicocelectomy: a triple-blind randomized controlled trial. Issue 6 (December 2020) - Abbasi, Behzad; Molavi, Newsha; Tavalaee, Marziyeh; Abbasi, Homayoun; Nasr-Esfahani, Mohammad H.
Abstract: Research question: Does supplementation with alpha-lipoic acid (ALA) enhance sperm parameters and/or the status of sperm lipid peroxidation and DNA fragmentation in men who have undergone microsurgical repair of a varicocele? Design: Individuals with a varicocele who had undergone varicocelectomy were divided into two groups receiving either 600 mg of ALA or an identical placebo for 80 days. Semen samples obtained from the participants before surgery and after completion of the course of medication were analysed and compared. Participants, clinicians and data analysts were blinded to the randomization sequence. Results: In the ALA group, total motility ( P  = 0.01) and progressive motility ( P  = 0.002) of the spermatozoa were significantly higher compared with the placebo group after surgery. Sperm lipid peroxidation and DNA damage (assessed by sperm chromatin structure assay) showed significant decreases in both the ALA and placebo groups ( P  ≤ 0.02) after treatment. Conclusions: An 80-day course of ALA medication after surgical repair improves total motility and progressive motility of the spermatozoa in individuals with a varicocele.